Roots of English exploring the history of dialects - Tagliamonte, Sali (Cambridge University Press, 2013)
"What is the explanation for the nature, character and evolution of the many different varieties of English in the world today? Which changes in the English language are the legacy of its origins and which are the product of novel influences in the places to which it was transported? Roots of English is a groundbreaking investigation into four dialects from parts of northern Britain out of which came the founding populations of many regions in other parts of the world. Sali Tagliamonte comprehensively describes and analyses the key features of the dialects and their implications for subsequent developments of English. Her examination of dialect features contributes substantive evidence for assessing and understanding bigger issues in sociolinguistic theory. Based on exciting new findings, the book will appeal to those interested in dialects, from the Anglophile to the syntactician"--Provided by publisher.